(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
The present study has been carried out in an attempt to observe the usefulness of peripheral blood buffy-coat microscopic examination for detection of LD-body from clinically suspected Kala-azar cases. Total 127 individuals are included in this study as cases and controls. Among them 67 are clinically suspected Kala-azar cases included from one of the Kala-azar endemic areas of Bangladesh and 60 are taken as endemic and nonendemic healthy controls. Peripheral venous blood and bone marrow aspirate collected and tested for LD bodies from clinically suspected Kala-azar cases in Rajshahi Medical College Hospital, during the period of July 2006 to June 2007. Serum from all cases and controls were tested by rK39 ICT for serological identification of visceral leishmaniasis. Laboratory examinations were performed in the Department of Microbiology and Immunology, BSMMU, Dhaka. Out of 67 study cases bone marrow smear microscopy for LD bodies positive in 44 (66.67%) and buffy-coat smear microscopy positive for 21 (31.34%); diagnostic sensitivity and specificity of buffy-coat smear microscopy was 47.72% and 100% in comparison with bone marrow examinations. Buffy-coat smear made form the 23 splenomegalic patients, microscopy revealed significant number 17 (73.91%) of the cases were positive for LD-body and all of the four hepato-splenomegalic patients were positive (p-value >0.05, reached from 2 test). Results of rK39 ICT for detection of visceral leishmaniasis cases show 100% sensitivity and 90% specificity. Peripheral blood buffy coat examination for LD body in splenomegalic cases of Kala-azar may replace bone marrow examinations. Bangladesh J Med Microbiol 2010; 03 (02): 27-32